Studi Karakteristik Masyarakat Dalam Menggunakan Moda Transportasi Bus Eksekutif Surabaya-Madiun - Putra Iswanto, Ary; Ahda Imron, Nanda; Handoko (Jurnal Keselamatan Transportasi Jalan (Indonesian Journal of Road Safety), 2021)
Transportation is very important in accelerating economic, social and cultural growth in a region. Surabaya is the capital of the province of East Java and is the largest city on the island of Java. Surabaya, which is the provincial capital, certainly provides various facilities to serve the community, especially in the field of mass transportation. Several modes of mass transportation that have developed in the city of Surabaya, one of which is a bus with routes to several small cities such as the cities of Madiun, Magetan and Ponorogo. In this study, the authors want to know the characteristics of the community in using the executive bus transportation mode which is considered to have a new fleet with the Surabaya-Madiun toll road. In this study using a questionnaire instrument method with Solvin, Issac micael and Morgan sampling techniques, then analyzed the data using a quantitative descriptive model. From the results of the study, it is known that the characteristics of executive bus users through the Surabaya-Madiun toll road are mostly male, aged 21-30 years, with a high school education background.